UPAYA PEMERINTAH DALAM MENGATASI PENCEGAHAN PENGEMIS DARI PERSEPEKTIF UNDANG-UNDANG KESEJAHTERAAN SOSIAL - Piran, Feliksya Weda; Mardjono, H.R. Adianto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Urban is the center of economics that causes widespread urbanization of people from villages to cities to free themselves from poverty. However, not all the people who participated in urbanization were accompanied by proper skills and education, so they had to work on a non-permanent basis to fulfill their daily needs. Because of the lack of skills and education, social problems arise, such as beggars. Hence, the government needs to do something to prevent and overcome that problem. The purpose of this research is to find out the government’s effort to prevent and overcome the existence of beggars, based on Undang-Undang No. 11 Tahun 2009. This research uses normative research or library research. This research also uses law and conceptual approach, that is reviewed based on several views and doctrines. The result of this research states that law enforcement through the provision of criminal law to beggars and homeless people is not running as it should. This is because criminal law is more about giving a punishment, not a treatment. However, the application of Undang-Undang Sistem Jaminan Sosial Nasional dan Undang-Undang Kesejahteraan Sosial Nomor 11 Tahun 2009 Pasal 34 is considered to be more effective in overcoming the poverty. Beside that, Peraturan Pemerintah Nomor 31 Tahun 1980 also provides a detailed explanation of efforts to overcome the existence of homeless people and beggars. Even though problems related to beggars are the responsibility of the government, participation from the community is also needed as donors so that they feel deterred from begging anymore